2012
DOI: 10.1111/j.1471-4159.2012.07922.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain region‐specific immunolocalization of the lipolysis‐stimulated lipoprotein receptor (LSR) and altered cholesterol distribution in aged LSR+/− mice

Abstract: Brain lipid homeostasis is important for maintenance of brain cell function and synaptic communications, and is intimately linked to age-related cognitive decline. Because of the bloodbrain barrier's limiting nature, this tissue relies on a complex system for the synthesis and receptor-mediated uptake of lipids between the different networks of neurons and glial cells. Using immunofluorescence, we describe the region-specific expression of the lipolysis-stimulated lipoprotein receptor (LSR), in the mouse hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…TJ proteins might not only be involved in sealing an epithelium or endothelium; they might have other functions. By using different fixation methods (PFA fixed tissue), LSR expression has been visualized in specific neuronal subpopulations ( Stenger et al, 2012b ). By performing filipin staining, the authors demonstrated an increase in membrane-associated free cholesterol in specific brain regions of 18-mo-old Lsr +/− mice compared with wild-type controls.…”
Section: Resultsmentioning
confidence: 99%
“…TJ proteins might not only be involved in sealing an epithelium or endothelium; they might have other functions. By using different fixation methods (PFA fixed tissue), LSR expression has been visualized in specific neuronal subpopulations ( Stenger et al, 2012b ). By performing filipin staining, the authors demonstrated an increase in membrane-associated free cholesterol in specific brain regions of 18-mo-old Lsr +/− mice compared with wild-type controls.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that neurons can produce and store LDs during autophagy, and there is evidence that certain neurons may store cholesterol, presumably in the form of esterified cholesterol, in droplet-like structures [24-26]. Because droplets are observed even in N41 cells with no detectable cell-surface LPL activity, it is likely that these cells have apoE-mediated mechanisms in place to take up lipid independent of LPL.…”
Section: Discussionmentioning
confidence: 99%
“…The series of arm entries were recorded visually, and arm entry was validated when the base of the tail of the mouse was completely placed in the arm. Alternation score was calculated as the ratio of the number of triads to the total number of possible alternations (defined as the number of arm entries minus two) [85].…”
Section: Methodsmentioning
confidence: 99%